​An exploration into how established South African Fashion Brand David Tlale are positioning their Brand within the market, compared to the South African Contemporary Fashion Brand Rich Mnisi. - Viggers, Domanique (The IIE, 2019)
The following research study is case-study based and explores the concept of brand positioning within the South African Fashion Industry. The aim of the study is to identify the different brand positioning strategies used by the established South African fashion brand, David Tlale and the contemporary South African fashion brand, RICH MNISI. The research was guided by a theoretical framework which is identified as the first step within the Strategic Management Process. The research was then informed by previous literature that focused specifically on brands, brand positioning, positioning of a fashion brand as well as African fashion innovation. The research methodology was then outlined and followed an interpretivist paradigm that focused on an exploratory research approach which aligns with the qualitative nature of the study. Data was collected through social artefacts that related directly to the identified brands. Data analysis was conducted through the means of content analysis as well as semiotic analysis of visual brand representations. The research found that the two fashion brand, David Tlale and RICH MNISI, used different but similar positioning strategies to position the brands within the South African fashion industry. The study aimed to contribute to the body of knowledge on positioning fashion brands in South Africa, and the strategic positioning strategies that may be used to do this.
Keywords: Brand; Brand positioning; Fashion industry; South African fashion industry; Fashion brand